A Deep Learning Approach with Feature Derivation and Selection for Overdue Repayment Forecasting - Bin Liu (Applied Sciences, 2020)
Risk control has always been a major challenge in finance. Overdue repayment is a frequently encountered discreditable behavior in online lending. Motivated by the powerful capabilities of deep neural networks, we propose a fusion deep learning approach, namely AD-MBLSTM, based on the deep neural network (DNN), multi-layer bi-directional long short-term memory (LSTM) (BiLSTM) and the attention mechanism for overdue repayment behavior forecasting according to historical repayment records. Furthermore, we present a novel feature derivation and selection method for the procedure of data preprocessing. Visualization and interpretability improvement work is also implemented to explore the critical time points and causes of overdue repayment behavior. In addition, we present a new dataset originating from a practical application scenario in online lending. We evaluate our proposed framework on the dataset and compare the performance with various general machine learning models and neural network models. Comparison results and the ablation study demonstrate that our proposed model outperforms many effective general machine learning models by a large margin, and each indispensable sub-component takes an active role.